2018
DOI: 10.11113/mjfas.v14n3.1070
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and characterization of self-nano emulsifying drug delivery systems of lemongrass (cymbopogon citratus) essential oil

Abstract: The present research was aimed to characterize the formula of self-nano emulsifying drug delivery systems (SNEDDS) for lemongrass essential oil. The observation variables included: particle size, zeta potential, and morphology. Meanwhile, the materials consisted of the mixtures of oils (lemongrass essential oil and carrier oil), surfactants, and cosurfactants. Carrier oils were screened as candidates for SNEDDS, and the formula was evaluated for transmittance and emulsification time. The value of the formulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 0 publications
1
14
0
1
Order By: Relevance
“…Administration of POH decreased glucose and increased Hb levels that led to a reduction in the HbA1c levels in diabetic rats when compared to the diabetic control group. Reports have shown that agents with antioxidant and free radical scavenging properties significantly inhibit protein glycation reactions associated with DM [35] This further supports the antidiabetic effect of POH.…”
Section: Discussionsupporting
confidence: 62%
“…Administration of POH decreased glucose and increased Hb levels that led to a reduction in the HbA1c levels in diabetic rats when compared to the diabetic control group. Reports have shown that agents with antioxidant and free radical scavenging properties significantly inhibit protein glycation reactions associated with DM [35] This further supports the antidiabetic effect of POH.…”
Section: Discussionsupporting
confidence: 62%
“…Drug delivery facilitated by SEDDSs are essentially influenced by droplet size, droplet size distribution and zeta-potential [ 41 , 63 , 64 ]. Size characterization is considered one of the most insightful experiments performed during the development of SEDDSs as size influences not only drug release, but also the stability of the SEDDS formulations [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Along with the formula generated in our previous study [26], SNEDDS were optimized using a D-Optimal mixture experimental designed and performed using a Design Expert® Ver. 7.1.5. software (Stat-Ease Inc., Minneapolis, USA) [27] by selecting the percentage of the oil component X1 (a mixture of VCO and Cymbopogon citratus essential oil), the surfactant X2 (Tween 80), and the co-surfactant (PEG 400) as independent variables, while emulsification time in sec (Y1) and transmittance in percent (Y2) as responses.…”
Section: Optimization Of Sneddsmentioning
confidence: 99%